Software-Reconfigurable System Supporting Point-to-Point Data Communication Between Vehicle Social Networks and Marketers - Fanbo Meng; Xiaoxue Gong; Lei Guo; Xintong Cai; Qihan Zhang (IEEE Access, 2017)
Social users can be flexibly covered by a vehicle traveling along a certain trajectory in a city. This scenario provides opportunities for marketers to utilize vehicles as recommenders targeting potential customers. As a result, the vehicle social network (VSN) concept emerges. Since a marketer usually operates from a remote central office (CO), an effective communication system is urgently required to support data transmission between VSNs and COs. Orthogonal frequency division multiplexing (OFDM) is a modulation technique characterized by high spectral efficiency and dispersion resistance, and intensity modulation and direct detection (IM/DD) is an effective solution for optical OFDM (OOFDM) data transmission. Performing discrete Fourier transform (DFT) and discrete Hartley transform (DHT) operations can enable the satisfaction of various transmission requirements between a VSN and a CO. In this paper, we support the above claims through theoretical and simulation-based analyses. Moreover, a software-reconfigurable platform is established to achieve flexibility between DFT and DHT functionalities. Thus, diverse transmission requirements can be satisfied by modifying individual modules deployed in a single smart system instead of using multiple rigid network architectures. Simulated and experimental results both demonstrate the feasibility and effectiveness of our solutions.